2015
DOI: 10.1146/annurev-publhealth-031914-122357
|View full text |Cite
|
Sign up to set email alerts
|

Tax-Exempt Hospitals and Community Benefit: New Directions in Policy and Practice

Abstract: The current community benefit standard for nonprofit hospital tax exemption has been the subject of mounting criticism. Many different constituencies have advanced the view that in its present form it fails to ensure that nonprofit hospitals provide adequate benefits to their communities in exchange for their tax exemption. In contrast, hospitals have often expressed the concern that the community benefit standard in its current form is vague and therefore difficult to comply with. Various suggestions have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 32 publications
0
58
0
Order By: Relevance
“…With the major changes to community benefit in 2009 and 2010, increased attention and experience with the new requirements have created an opportunity for scholars and practitioners to offer suggestions as to how community benefitrelated policy might be further modified. An early summary of policy proposals suggested three categories: transparency, accountability, and population health (7). This scoping review found leveraging community benefit for population health to be the most frequent policy recommendation.…”
Section: Policy Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the major changes to community benefit in 2009 and 2010, increased attention and experience with the new requirements have created an opportunity for scholars and practitioners to offer suggestions as to how community benefitrelated policy might be further modified. An early summary of policy proposals suggested three categories: transparency, accountability, and population health (7). This scoping review found leveraging community benefit for population health to be the most frequent policy recommendation.…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…Most non-profit hospitals in the U.S. conducted their first required CHNA in 2013. Second, the expansion of Medicaid and the inclusion of guaranteed issue creates an environment similar to that following the original passage of Medicare and Medicaid, wherein many question whether tax-exempt status is justified given the possible decrease in charity care (6)(7)(8)(9)(10). Finally, the ACA's promotion of population health, primarily through new payment mechanisms, creates a possibility of expanding the notion of community benefit to include social determinants of health.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, some evidence already exists that the Medicaid eligibility reforms that many states have adopted are having such an impact. At present, hospitals are not required to reinvest any savings from reduced uncompensated costs but, as noted, there is some expectation that hospitals will redirect at least some of the savings toward programs and infrastructure targeted at upstream determinants of health (Hester et al 2015;Rubin, Singh, and Young 2015). As such, in the near future, the community benefit activities of tax-exempt hospitals may play an increasingly important role in the funding of population health initiatives for communities across the United States (Kindig and Isham 2014;Singh et al 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…13 Hospitals' financial contributions to the larger public health system, however, vary substantially across states. In some states, hospitals contribute almost nothing to funding population health activities, whereas in other states, the amount of hospitals' contributions plays an important role in the funding of community health initiatives.…”
Section: Table 3 • Gini Coefficients For Hospital Communitymentioning
confidence: 99%
“…11,12 Recent efforts to increase transparency around hospitals' community benefit spending in the form of revisions to IRS Form 990 Schedule H, however, may put pressure on hospitals to maintain their pre-ACA levels of community benefit investment by making changes to the composition of the benefits they provide. 13 Little is currently known about the importance of hospitals' community benefit dollars as a funding source for improving population health. Building on 2 recently published studies of hospital community benefit, this article aims to shed light on this question.…”
mentioning
confidence: 99%